2014
DOI: 10.5812/hepatmon.13100
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Transforming Growth Factor Beta 1-509C/T and +915G/C Polymorphisms and Chronic Hepatitis B in Iranian Patients

Abstract: Background:Chronic hepatitis B is one of the world's major health concern. The etiological agent of this infection is hepatitis B virus (HBV), which can evade the immune system response. Transforming growth factor beta 1 (TGF-β1) can act against HBV by suppressing the viral replication. The TGF-β1 also plays an important role in preventing liver damage in chronically HBV infected patients.Objectives:In this study, the association of TGF-β1 +915G/C and -509C/T gene polymorphisms with chronic hepatitis B was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In a different tune, Kimura et al have demonstrated − 509C allele to be associated with a higher clearance rate of HCV as well as with lower promoter activity ( Kimura et al, 2006 ). However, in the contest of hepatitis B and Iranian patients, absence of association between TGF-β1 − 509C > T and + 915G > C polymorphisms with chronic hepatitis B indicated that these changes do not play a significant role in increasing the risk of chronic infection in Iranian patients ( Razavi et al, 2014; Romani et al, 2011 ). Our finding of TGF-β1 polymorphism at position − 509 with increase in C > T genotype in the patient group suggests its protective role, since all the patients recovered.…”
Section: Discussionmentioning
confidence: 99%
“…In a different tune, Kimura et al have demonstrated − 509C allele to be associated with a higher clearance rate of HCV as well as with lower promoter activity ( Kimura et al, 2006 ). However, in the contest of hepatitis B and Iranian patients, absence of association between TGF-β1 − 509C > T and + 915G > C polymorphisms with chronic hepatitis B indicated that these changes do not play a significant role in increasing the risk of chronic infection in Iranian patients ( Razavi et al, 2014; Romani et al, 2011 ). Our finding of TGF-β1 polymorphism at position − 509 with increase in C > T genotype in the patient group suggests its protective role, since all the patients recovered.…”
Section: Discussionmentioning
confidence: 99%
“…The enrolled subjects were individuals referred to the Taleghani hospital of Tehran from January 2010 to October 2011. The cases and controls sample size was calculated based on a previously published formula ( 26 , 27 ). Informed consent was obtained from all subjects at the time of enrollment and the ethical review boards of the institution approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that C-509T gene polymorphisms in the promoter region of TGF-β1 are associated with plasma levels (Hosseini Razavi et al, 2014 ). Similarly, the TGF-β1 T869C polymorphism affects the secretion of TGF-β1, suggesting that the polymorphic variants of TGF-β1 might influence cancer risk (Peng et al, 2011 ).…”
Section: Dysregulation Of Tgf-β In H Pylori -Indumentioning
confidence: 99%